2010
DOI: 10.1039/b919285a
|View full text |Cite
|
Sign up to set email alerts
|

New strategies for selectively synthesizing cubic boron nitride in hydrothermal solutions

Abstract: By developing new strategies, cubic boron nitride crystals (cBN) were selectively synthesized by a hydrothermal method using H 3 BO 3 , NH 3 $H 2 O and N 2 H 4 $H 2 O as the reactants. The experimental results indicated that both the relative content and crystalline perfection of cBN were improved by increasing the reaction temperature. Furthermore, we developed two new strategies, i.e., pressurizing the reaction solution (with nitrogen) and quickly cooling down thereafter. As a result, cBN content and its cry… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 26 publications
(23 reference statements)
0
12
0
Order By: Relevance
“…As reported by Xing et al, the hBNQDs could be synthesized via the normal hydrothermal reaction starting from H 3 BO 3 (boron source) and NH 3 ·H 2 O (nitrogen source) at 200 °C ( Scheme a), but it is not applicable for the growth of hBNNS. As is well known, the halides have the ability to etch BN, including hBN and cBN, and have been found to be effective in the selective synthesis of cBN crystals . Inspired by the hBNQDs synthesis and the halides effect, we proposed the HAHTA synthetic method for the synthesis of hBNNS (Scheme b).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…As reported by Xing et al, the hBNQDs could be synthesized via the normal hydrothermal reaction starting from H 3 BO 3 (boron source) and NH 3 ·H 2 O (nitrogen source) at 200 °C ( Scheme a), but it is not applicable for the growth of hBNNS. As is well known, the halides have the ability to etch BN, including hBN and cBN, and have been found to be effective in the selective synthesis of cBN crystals . Inspired by the hBNQDs synthesis and the halides effect, we proposed the HAHTA synthetic method for the synthesis of hBNNS (Scheme b).…”
Section: Resultsmentioning
confidence: 99%
“…As is well known, the halides have the ability to etch BN, including hBN and cBN, [47] and have been found to be effective in the selective synthesis of cBN crystals. [43] Inspired by the hBNQDs synthesis and the halides effect, we proposed the HAHTA synthetic method for the synthesis of hBNNS (Scheme 1b). With respect to the possible mechanism, the edges of the hBNQDs formed at the initial stage of HAHTA may be activated by the halides etching, which may reduce the energy barrier for the further growth of hBNNS, and the continuous hydrothermal assembly gave rise to the final evolution from 0D hBNQDs to 2D hBNNS.…”
Section: Possible Mechanism For the Halides-assisted Growthmentioning
confidence: 99%
See 1 more Smart Citation
“…These results show that compared to cBN, hBN was preferentially etched in fluorinecontaining environment and the improved etching selectivity would facilitate the synthesis of high-quality cBN films via the chemical vapor deposition route. In addition, we also reported that halide species had obvious induction effect of cBN synthesis with NaN 3 and NH 3 as nitrogen-sources in hydrothermal condition [22,23]. Furthermore, for enlarging the applicability of induction effect in different nitrogen-source system, in this paper, we investigated the synthesis of cBN with N(CH 3 ) 3 as nitrogen source in hydrothermal condition.…”
mentioning
confidence: 90%
“…The BN originally exists in several crystal structures such as wurtzite BN (w-BN), cubic BN (c-BN), rhombohedral BN (r-BN), hexagonal BN (h-BN), explosive BN (e-BN), and turbostratic BN (t-BN). The c-BN and w-BN are especially known for super-hardness, wide band gap and its oxidation resistance which makes them a promising material for fabrication of cutting tools, protective coatings, and optoelectronic devices [4,5].…”
Section: Introductionmentioning
confidence: 99%